PENGARUH TRANSPARANSI, AKUNTABILITAS, DAN RESPONSIBILITAS PENGELOLAAN KEUANGAN SEKOLAH TERHADAP KINERJA GURU - Utama, Daniel Aditya; Setiyani, Rediana (Fakultas Ekonomi, Universitas Negeri Semarang, 2014)
Good governance is the management governance principles which can support the performance improvement. The objective of the study was to know the influence of transparency, accountability, and responsibility of school financial management on teachersâ performance at SMP (State Junior High Schools) Ex-RSBI in Semarang, either simultaneously or partially. The population of the study was all teachers at SMP Ex-RSBI in Semarang; they were 191 teachers. The data were collected by questionnaires and interviews. The data were analyzed by descriptive analysis, and the hypotheses were tested by multiple regression analysis. Based on the research results, it showed that the transparency, accountability, and responsibility of school financial management contributed on teachersâ performance for 24.8%. Partially, there was only the responsibility variable of school financial management which contributed significantly on teachersâ performance for 4.368%.